A RISK ASSESSMENT MODEL FOR HEALTH SUPPLY CHAIN BASED ON HYBRID FUZZY MCDM METHOD - Hosseinpour, Mahmood; Amirkhan, Mohammad; Rezaeian, Javad; Doostideilami, Mohammadjafar (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
This study aims to identify and evaluate the risks of the manufacturing sector in the health supply chain of the food industries. For this purpose, first, the risks related to food industry units have been identified using the fuzzy Delphi approach and then, applying the fuzzy best-worst model (F BWM) and the fuzzy decision-making trial and evaluation laboratory (F DEMATEL) model, the weights and internal relationships of criteria have been determined, respectively. For the final prioritization of the risks, a hybrid method based on F BWM and F DEMATEL has been used. To demonstrate the applicability of the proposed approach, a real case of food industry units is presented. The data are both quantitative and qualitative, and both library and field methods have been used to collect them. The results showed that among the identified factors, the biological factor had the highest priority, and the health factor had the lowest one.